Incorporação de Ag/Zeólitas em filmes de quitosana para o tratamento de queimaduras - Yassue-Cordeiro, Patricia Hissae (2014)
Chitosan polymeric films are used as wounding dressing for burns and wounds. Antimicrobial properties of these films can be induced or potentiated with incorporation of changed zeolite or impregnated with silver or silver sulfadiazine. Films were prepared by dispersion of chitosan solution containing zeolite with silver (Ag- Zeolite) in a plan surface and slowly drying. Studied variables on filme preparation were: associated silver or not associated (silver nitrate and silver sulfadiazine); silver not associated (ion exchange and moist impregnation) and the kind of zeolite (Y and A). Zeolite ratio Si/Al was determined by RMN analysis of 29Si and the elementary composition was determined by analysis of x-ray fluorescence by total reflection (SR-TXRF) and energy dispersive spectroscopy (EDX). Both Zeolite-Ag and polymeric films were performed textural analyzes, scanning electron microscopy (MEV), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (DRX), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Chitosan polimeric films with Ag-Zeolite applicability were evaluated by performing mechanical properties analysis, vapor barrier to water and microorganisms, color analysis, silver releasing and antimicrobial properties in solid medium for Ag-Zeolite and liquid medium for Ag-Zeolite films. Chitosan film with 5AgA-TI-B (zeolite type A exchanged with 5% silver) showed the best properties for use in wounding burn dressings, with high antimicrobial activity due the high silver composition and location both in the zeolitic surface in clusters forms and inside the channels and cavities fo the zeolite A, showing a controlled release of silver ions, therefore, presenting higher antimicrobial ratios. This film exhibit good water vapor permeation property, as like others wounding dressings found in the market and permeation through the membrane of microorganisms does not occur, showing capability of prevent infections of bacteria and fungi in the burn wound and presented the best mechanical properties showing lower values of Young's modulus and tensile strength when compared with films of pure chitosan and higher percent elongation when compared with other polymer films synthesized in this work, showing a better suppleness and flexibility for use as dressings for burns.